Electrocardiographic changes in QTc interval and other parameters associated with osimertinib therapy - Pan, Yilin; Peng, Kexin; Jiang, Yichuan; Yang, Ping; Du, Beibei; He, Yuquan (Frontiers in Oncology, 2025)
IntroductionOsimertinib, a third-generation EGFR-TKI, is approved for the first-line treatment of EGFR-mutated advanced NSCLC and for T790M-positive NSCLC after progression on previous EGFR-TKI therapy. Osimertinib is associated with cardiotoxicity, including severe QT interval prolongation, which necessitates detailed evaluation due to its increasing use.MethodsThis retrospective, single-center study conducted at Jilin University China-Japan Union Hospital evaluated electrocardiographic changes with EGFR-mutated NSCLC treated with osimertinib. The study consecutively included 102 patients diagnosed with NSCLC at the China-Japan Union Hospital of Jilin University from August 1, 2019, to December 31, 2022. Among them, 41 patients who had both pre- and post-treatment ECG records while receiving osimertinib (80 mg daily) were analyzed. ECG parameters such as heart rate, PR interval, QRS duration, QRS axis, and QT intervals were manually calculated and analyzed.ResultsThe study population had a mean age of 68.56 ± 8.73 years, comprising 46.34% males. Significant changes were observed in the QTc Bazett interval (P < 0.0001), QTc Fridericia interval (P = 0.0002) and QRS axis (P = 0.0387) post-treatment. QT interval prolongation was significant (McNemar test P = 0.0039), with both QTc Bazett and QTc Fridericia intervals showing notable prolongation. However, the changes in heart rate, PR interval, and QRS duration were not statistically significant.ConclusionThis study comprehensively investigates the electrocardiographic changes before and after osimertinib treatment in patients with EGFR-mutated NSCLC. The significant prolongation of QTc intervals underscores the need for rigorous ECG monitoring to mitigate potential cardiotoxicity.